Effect of approach speed on soccer shooting performance - Ou, Y.-C.; Cheng, K. B. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate the effect of different initial conditions (approaching speeds) on soccer shooting performance (indicated by ankle speed at ball impact). Three initial conditions, including standing still, walking and running at self-selected speeds, were adopted for performing kicking. The results showed that the running condition, with the greatest approaching speed, led to the highest ankle speed for generating the fastest ball speed after impact. The current results will be used for building a mathematical model for simulating soccer shooting with various approach speeds.